Humanism in the Context of General Philosophy: Upholding Human Freedom and Potential - Zahraa, Afiqah; Sipahutar, Yura Marizka; Al-hafizh, Muhammad; Syahputra, Heru (Jurnal Penelitian Medan Agama, 2024)
This study explores the concept of humanism in general philosophy, a theme that has been central to philosophical thought since the Renaissance. The main focus is on how humanism, as a human-centered worldview, offers solutions to the crises of values and morality in modern life. This research employs a qualitative method with a library research approach, involving critical analysis of philosophical texts influential in the development of humanism, including the ideas of key humanist figures. The findings reveal that humanism in general philosophy emphasizes the importance of individual freedom, moral autonomy, and human responsibility in creating a more meaningful world. Based on the analysis of various literature, this study concludes that the concept of humanism remains relevant as a framework for addressing global challenges such as social injustice and environmental crises, as well as for fostering justice and equality.